Livro: Queimaduras em unidades de alimentação e nutrição - ensinando minha equipe a prevenir acidentes em ambiente laboral - Medeiros, Tais Adorna De [UNIFESP] (2021)
Introduction: The causes of burns belonging to the 15 main causes of trauma in adults and are very common in some work environments, such as Food and Nutrition Units (UANs). Workplace Safety Programs aim to raise employee awareness of the protection of their lives and their partners by means of safe actions. Objective: development of a digital book on occupational safety care to prevent burns in UANs. Method: This is a descriptive, exploratory study. The work followed the phases of the Design Thinking methodology. In the “discover” phase, the Desk research was carried out: searching for precedence over the internet, in the electronic databases PubMed / Medline, Latin American and Caribbean Literature in Health Sciences (LILACS), EMBASE and in the electronic library Scientific Electronic Library On-line (SciELO) and Google, about books, spelling book, manuals on the topic of preventing burns in UANs and the application of work safety training. Afterwards, a bibliographic survey was carried out in the electronic databases previously mentioned, through the descriptors: burns, health education, healing, occupational health, occupational risks and accident prevention, in the last ten years, in Portuguese, English and Spanish for further development of the content. In “Define”, the writing of the book's pilot was defined and carried out. In the “Develop” phase, the book's content was validated by specialists, according to the Delphi Technique and Content Validation Index (IVC), and in the “Deliver” phase, a review of the Portuguese language, visual communication, graphic design, diagramming was carried out and requested. the International Standard Book Number (ISBN). Results: The search for priority did not find materials with a focus on training and practical activities in occupational safety. The content was developed and structured in five chapters. It was validated by specialists, through an online questionnaire and obtained a Global IVC greater than 0.90, which shows that the book meets the objectives proposed for its elaboration and in this way it will be able to develop the way in which managers train their operational teams. Conclusion: The book entitled: "Burns in Food and Nutrition Units - teaching my team to prevent accidents in the workplace" was developed and validated.